E-Voting System for Election with Mobile Based Apps - Reydho Trihandika Putra; Dhiyaa Rifqi Taufiqurrahman; Kevin Junaedi H Sagala (Universitas Komputer Indonesia, 2023)
Election is an important moment for the democratic process in Indonesia, Indonesia has held elections regularly for a long time. Election in Indonesia still carried out conventionally by coming to Tempat Pemungutan Suara (TPS) or Voting Place to vote. The purpose of this research is to design a mobile based election e-voting system as means to conduct elections for head of state or region and make it easier for the people to vote without having to travel. The research method used in this research is descriptive analysis with a qualitative approach. The result of this research is to show that the E-PIL application can make it easier for Komisi Pemilihan Umum (KPU) to carry out election (pemilu) also make it easier for the people to vote only by accessing E-PIL application that can be accessed via each smartphone. The main concept of this application is e-voting feature for election that can be used in every election agenda. Also makes it easier for the KPU in voting process because E-PIL application can only be used by 1 ID on 1 device that integrated with the government. In the end, E-PIL application is present as a medium for elections as well as to adapt in today’s digital world